The First report of metals and metalloids on bone and claw tissues of Humboldt penguins (Spheniscus humboldti) - Adesina, Kolawole E.; Espejo, Winfred; Celis, José; Sandoval, Marco; Specht, Aaron J. (Austral Journal of Veterinary Sciences, 2024)
Samples of bones (humerus) and claws of adult Humboldt penguins (Spheniscus humboldti) were opportunistically obtained from twenty-seven carcasses at two important nesting sites in northern Chile: Chañaral Island (CHI) and Pan de Azúcar Island (PAI). The concentrations of trace elements (Cu, Zn, Pb, Ni, Fe, Se, As, Br, Mn and Cr) were determined by X-ray fluorescence. The highest levels (mean ± standard deviation, μg/g dry weight) of Cu (26.57 ± 4.08), Zn (163.9 ± 42.7), Pb (1.86 ± 1.53), Ni (0.31 ± 0.03), Se (7.70 ± 4.87) and Cr (0.25 ± 0.24) were detected in bones, whereas the highest levels of Fe (3,162 ± 1,579), As (6.75 ± 4.21), Br (0.12 ± 0.06) and Mn (76.7 ± 47.9) were found in claws. In bones, Se and Ni levels were higher (P < 0.05) in CHI than in PAI. In claws, the contents of Pb, Fe, and Mn were higher at CHI than those at PAI, whereas only As exhibited higher contents at PAI than those found at CHI. The trace element content in the claws and bones found herein may be the result of either acute or chronic exposure to penguins, respectively. These findings may serve as a baseline for further studies to design adequate and opportune plans to protect this vulnerable species.